"Using the Language of Christian Love and Charity": What Liberal Religion Offers Higher Education in Prison - Atkins, Charles (Religions, 2019)
This article explores what religious frameworks and institutions have to contribute to college-in-prison. We first provide an historical overview of higher education programs in American prisons. Then, we limn the role religion can play in motivating people to commit themselves to educating incarcerated people. Because this work is so thorny, we document some of the generic challenges programs must face and show how religious languages can be an asset in navigating these challenges. Next, we present the pedagogical practices and educational philosophies expressed among the programs in our study. We conclude with some broader reflections about teaching incarcerated people, and, after wrestling with objections, we encourage our colleagues in religious studies-those with faith commitments as well as those without them-to get involved.